Analysis of the competencies and learning outcomes concepts of virtual environments - García, Javier (Universidad Panamericana, Escuela de Comunicación, 2021)
The present article focuses on the presentation of a proposal for the definition of the concepts used in our learning model in virtual environments referred as competencies and learning outcomes, based on an analysis of the existing bibliography in English, Spanish and Russian and the experience accumulated during 7 years of work in this modality.
Análisis de los conceptos de competencias y resultados de aprendizaje de entornos virtuales
Introduction -- Problem statement -- Bibliographic review -- Discussion -- ASB 2019 strategic planning for business -- Conclusions
Keywords: Competencies; Learning outcomes; Virtual environments; SOCIALES Y ECONÓMICAS; Comunicación